Enhancing the Antioxidant Potential of Weissella confusa PP29 Probiotic Media through Incorporation of Hibiscus sabdariffa L. Anthocyanin Extract - Natalia Simionescu; Anca-Roxana Petrovici (MDPI AG, 2024)
Lactic acid bacteria (LAB) produce important metabolites during fermentation processes, such as exopolysaccharides (EPS), which represent powerful natural antioxidants. On the other hand, H. sabdariffa L. anthocyanin extracts protect LAB and support their development. This study uncovers for the first time, the antioxidant profile of Weissella confusa PP29 probiotic media and focuses on elevating its impressive antioxidant attributes by synergistically integrating H. sabdariffa L. anthocyanin extract. The multifaceted potential of this innovative approach is explored and the results are remarkable, allowing us to understand the protective capacity of the fermented product on the intestinal mucosa. The total phenolic content was much lower at the end of the fermentation process compared to the initial amount, confirming their LAB processing. The DPPH radical scavenging and FRAP of the fermented products were higher compared to ascorbic acid and antioxidant extracts, while superoxide anion radical scavenging and lipid peroxidation inhibitory activity were comparable to that of ascorbic acid. The antioxidant properties of the fermented products were correlated with the initial inoculum and anthocyanin concentrations. All these properties were preserved for 6 months, demonstrating the promising efficacy of this enriched medium, underlining its potential as a complex functional food with enhanced health benefits.